TO WHAT EXTENT DOES CUSTOMERS’ PERSPECTIVE INFLUENCE BANKING LIQUIDITY? AN APPLIED RESEARCH ON A SAMPLE OF COMMERCIAL BANKS LISTED ON THE IRAQ STOCK EXCHANGE - Ahmed Ali Kurd; Dured musa mahmoud; Ibrahim Ali Kurdi (American Journals, 2023)
The research aims to demonstrate the impact of customers’ perspective on the bank’s liquidity. The study relied on a descriptive study approach to study the reality of commercial banks. The study sample was based on the inductive and deductive method in defining a problem and giving a theoretical framework on the nature of the relevant international standards and their impact. The analytical method was relied upon through The researchers provided a practical framework for the most common banking performance indicators for analyzing the financial data of the commercial banks in the study sample, as banks were selected from the banking sector within the commercial banks listed on the Iraq Stock Exchange, namely (the Bank of Baghdad, the Assyria International Investment Bank, and Trans-Iraq Bank). . For the period from 2017 to 2020, the study concluded with a number of general and specific recommendations for the commercial banks sampled in the study, the most important of which was the necessity of applying and giving priority to the perspective of.
Keywords: Customer perspective, banking performance, Iraqi commercial banks.